1996
DOI: 10.3354/meps130135
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative variation of secondary metabolites in the sea hare Aplysia parvula and its host plant, Delisea pulchra

Abstract: tVe measured quantitative variation of structurally siinllar halogenated furanones in the sea hare Aplysia parvula (Opisthobranchia; Anaspidea) and in its host alga Delisea pulchra (Rhodophyta; Bonnemaisonales). Mean total levels of furanones from D. pulchra in A. parvula were 13.3% of the dry weight of the sea hares, with one metabolite comprising on average 86% of the total metabolite load of the sea hares. Levels of furanones in the sea hares were highest in the digestive gland but were also found in other … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
70
1
2

Year Published

1998
1998
2011
2011

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(82 citation statements)
references
References 26 publications
9
70
1
2
Order By: Relevance
“…Chemical defences in sea hares consist of ink and opaline secretions and, possibly, their skin, and mucous secretions which coat the skin. Secondary metabolites from Delisea pulchra and Laurencia obtusa have been detected in the mucous, skin and opaline secretions of Aplysia parvula (de Nys et al 1996, Rogers et al 2000a, which is consistent with a defensive role for acquired metabolites. A. parvula also differentially accumulate high concentrations of the metabolites palisadin A and furanone 3 from these red algae (Rogers et al 2000a).…”
Section: Introductionsupporting
confidence: 51%
See 1 more Smart Citation
“…Chemical defences in sea hares consist of ink and opaline secretions and, possibly, their skin, and mucous secretions which coat the skin. Secondary metabolites from Delisea pulchra and Laurencia obtusa have been detected in the mucous, skin and opaline secretions of Aplysia parvula (de Nys et al 1996, Rogers et al 2000a, which is consistent with a defensive role for acquired metabolites. A. parvula also differentially accumulate high concentrations of the metabolites palisadin A and furanone 3 from these red algae (Rogers et al 2000a).…”
Section: Introductionsupporting
confidence: 51%
“…Stachowicz & Hay 1999). A. parvula may augment these physical defences (and gain a direct benefit) by incorporating algal secondary metabolites into their skin, mucous and opaline secretions (de Nys et al 1996, Rogers et al 2000a, making them unpalatable to some potential predators, as suggested by the rejection behaviour of individual fishes in this study. This deployment of algal secondary metabolites on the body surface may also have indirect benefits by acting as an olfactory camouflage against predators that hunt by smell.…”
Section: Predation By Fishesmentioning
confidence: 90%
“…Concentrations of secondary metabolites are generally higher at distal portions in algae, soft corals, gorgoni-ans, and trees (Coley 1983, Harvell & Fenical 1989, Wylie & Paul 1989, Meyer & Paul 1995, de Nys et al 1996, but see . Structural materials usually follow a contrasting pattern, decreasing in concentration from the distal end to the base.…”
Section: Discussionmentioning
confidence: 99%
“…While several studies have examined quantitative variation in algal secondary chemistry (Carlton et al 1989, 1995, de Nys et al 1996, Puglisi & Paul 1997, Matlock et al 1999, few have examined the effects of within-algal variation on the feeding preferences of mesograzers (Van Alstyne 1989, Poore 1994, Cronin & Hay 1996a. Such studies are necessary not only to understand the factors affecting the production of chemical defenses, but also to provide insight into the ecological consequences of such variation (Hay 1996, Becerro et al 1998.…”
Section: Introductionmentioning
confidence: 99%
“…The sea hare Aplysia parvula is an oligophagous herbivore that feeds primarily on red algae (Carefoot 1987, Rogers et al 1995 and is able to sequester algal metabolites from its diet that have been hypothesized to function in defense against predators (Faulkner 1992, de Nys et al 1996. Switzer-Dunlap (1978) reported that, in laboratory cultures, larvae of A. parvula preferentially metamorphose in the presence of Portieria hornemannii (= Chondrococcus hornemanni) relative to other algae.…”
Section: Introductionmentioning
confidence: 99%